Sonoporation‐Enhanced Delivery of STING Agonist Induced Robust Immune Modulation and Tumor Regression. Issue 10 (24th August 2021) - Xu, Jun; Solban, Nicolas; Wang, Yun; Ferguson, Heidi; Perera, Samanthi; Lin, Ken; Cai, Mingmei; Paul, Miller; Schutt, Ernest G.; Larsen, Clayton T.; Li, Rhodemann; Saklatvala, Robert; et al.
Abstract: Sonoporation, the temporal cell membrane openings that can arise after ultrasound exposure, has been explored across many preclinical applications but has lacked translational momentum. This can be attributed to a lack of quantitative characterization of the sonoporation process. Additionally, the impact of sonoporation on modulating the tumor microenvironment is not well understood. Using a cyclic dinucleotide‐based STING (stimulator of interferon genes) agonist, MSA‐1, that is analogous to MK‐1454, and approved microbubbles and diagnostic ultrasound, the authors report a 5 min sonoporation procedure enhanced the tumor local concentration of systemically administered MSA‐1 by 6.58‐fold 15 min post sonoporation. The improved pharmacokinetic profile translates into greater STING‐mediated cytokine production, including TNF‐α, IFN‐α, and IFN‐β. Furthermore, through immunophenotyping, the authors report sonoporation could sustain STING‐mediated immune activation while reversing its impact on immune suppression. In both unilaterally and bilaterally inoculated syngeneic tumor models, the authors demonstrate that the sonoporation treated group significantly outperformed other controls at equivalent dosing conditions. These findings may further the understanding of the sonoporation process and its impact on immune modulation, which will accelerate the translational momentum of sonoporation. Abstract : A 5 min clinically translatable sonoporation procedure using United States Food and Drug Administration‐approved microbubbles and commercially available diagnostic ultrasound enables the systemic delivery of cyclic dinucleotide‐based STING agonist MSA‐1 and regressed both unilaterally and bilaterally inoculated syngeneic tumors as a result of improved pharmacokinetic/pharmacodynamic and immune modulation.